1980
DOI: 10.1109/tap.1980.1142269
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and numerical techniques for analyzing an electrically short dipole with a nonlinear load

Abstract: An electrically short dipole with a nonlinear dipole load is analyzed theoretically using both analytical and numerical techniques. The analytical solution is given in terms of the Anger function of i morder and imaginary argument and is derived from the nonlinear differential equation for the "Ikvenin's equivalent circuit of a dipole with a diode. The numerical technique is to solve the nodal equation using a timestepping finite difference equation method. The nonlinear resistance of the diode is treated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 6 publications
1
40
0
Order By: Relevance
“…Kanda [12] analyzed the response of a diode detector using the equivalent circuit model for the probe as shown in Fig. 2.…”
Section: A Validation Of the Probe Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Kanda [12] analyzed the response of a diode detector using the equivalent circuit model for the probe as shown in Fig. 2.…”
Section: A Validation Of the Probe Numerical Modelmentioning
confidence: 99%
“…Several recent studies have reported errors when measuring pulse-based RF signals as well as digitally modulated signals (e.g., IEEE 802.11b, IEEE 802.16e, WCDMA) using wideband electric-field probes typically employed in electromagnetic compatibility measurements and electromagnetic exposure assessments [7]- [11]. Kanda [12] performed analytical and numerical analysis of an electrically short dipole loaded with a diode detector in the presence of an incident CW signal. He derived the closed-form expressions for the response of the diode detector as a function of the incident signal showing the transition from square-law detection region to linear detection region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20(b) can be simplified as shown in Fig. 20(c), since the loop capacitance and diode capacitance are much smaller than the external capacitors C, resonant frequency and Q of the simplified equivalent circuit are given by I fo 2 r'NC3 -(C3 R) (31) and Q 2= La R (32) where C3 is the net capacitance of the two capacitors Cl and C2 in series.…”
Section: I1-mentioning
confidence: 99%
“…At present there is considerable interest in developing efficient methods for the analysis of non-linearly loaded antennas.This problem is of importance since non-linear effects must be taken into account in systems of antennas which include semiconductor componentslintegrated circuits and voltage limiters with very strong incident fields such as those produced by lightning or by NEMP (Nuclear ElectroMagnetic Pulse) [1] .Moreover,some field measurement techniques such as the EDM (Energy Density Meter) now being deve loped at the National Bureau of Standards [2] make use of short dipoles loaded by a diode-.It must also be noted that some radar applications with co-o perative targets are based on the use of non-linearly loaded scatterers [3].…”
Section: Introductionmentioning
confidence: 99%